1985
DOI: 10.1007/bf00238961
|View full text |Cite
|
Sign up to set email alerts
|

Interaction between inhibitory pathways to principal cells in the lateral geniculate nucleus of the cat

Abstract: Inhibitory interactions between interneurones of the lateral geniculate nucleus (LGN) of the cat were studied with an indirect method based on intracellular recordings of synaptic responses in principal cells. Recurrent inhibitory postsynaptic potentials (IPSPs), evoked by antidromic activation of principal cell axons in the visual cortex, were depressed by a preceding stimulation of the optic tract or the visual cortex. Disynaptic feed-forward IPSPs, evoked by optic tract stimulation, were likewise depressed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
88
0

Year Published

1985
1985
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 108 publications
(94 citation statements)
references
References 38 publications
6
88
0
Order By: Relevance
“…Consistent with the reduction in dLGN spiking generated by electrical (Marrocco et al, 1982;Ahlsén et al, 1985) or transcranial magnetic stimulation of V1 (de Labra et al, 2007), as well as previous reports in the mouse visual system (Olsen et al, 2012), we found that synchronous activation of Ntsr1 cells elicits reduction in spike count, presumably through activation of RE or local inhibitory input to dLGN relay cells. However, Ntsr1 activity does not always result in net inhibition, as evidenced by our Arch experiments removing Ntsr1 activity.…”
Section: Putative Mechanismssupporting
confidence: 92%
“…Consistent with the reduction in dLGN spiking generated by electrical (Marrocco et al, 1982;Ahlsén et al, 1985) or transcranial magnetic stimulation of V1 (de Labra et al, 2007), as well as previous reports in the mouse visual system (Olsen et al, 2012), we found that synchronous activation of Ntsr1 cells elicits reduction in spike count, presumably through activation of RE or local inhibitory input to dLGN relay cells. However, Ntsr1 activity does not always result in net inhibition, as evidenced by our Arch experiments removing Ntsr1 activity.…”
Section: Putative Mechanismssupporting
confidence: 92%
“…It has recently been suggested that the recurrent inhibitory system may function as a variable gain regulator for the transmission through the d.l.g.n. (Ahlsen et al 1983a). With the recurrent pathway operative the dynamic range of the visual signals passing through the nucleus will be reduced compared to the situation without recurrent inhibition.…”
Section: Discussionmentioning
confidence: 99%
“…Likewise, an external influence on the recurrent interneurones is a prerequisite for the suggested gain control of the transmission through the d.l.g.n. (Ahlsen et al 1983a). …”
Section: Introductionmentioning
confidence: 99%
“…The cortico-geniculate pathway forms one limb in a disynaptic recurrent excitatory system, earlier proposed to serve as a neuronal gain regulator used to enhance signal transmission through the l.g.n. during visual attention (Ahlsen, et al 1985). By the additional projection to layer 4 simple cells, the main cortical target of principal cells, the gain increasing capacity of the layer 6 system would be greatly improved without jeopardizing the stability of the circuits.…”
Section: Functional Considerationsmentioning
confidence: 99%